Henry L. Abbot family papers - Abbot, Henry L.
Correspondence, memoirs, diaries, writings, photographs, legal and financial records, biographical and genealogical material, military records, ships logs, maps, printed matter, mementos, and other papers primarily documenting Henry L. Abbot's service as topographical engineer and officer in the Union Army and family life and social activities in Massachusetts during the Civil War.
Subjects include the First Battle of Bull Run, construction of fortifications around Washington, D.C., the Peninsular Campaign of 1862, U.S. Army movements during the sieges of Petersburg and Richmond, Va., in 1864 and 1865, Abraham Lincoln's administration, African American soldiers, religion, Union commanders, ordnance technology, causes of the war, the Emancipation Proclamation, Ulysses S. Grant's situation in Virginia, George B. McClellan's presidential bid, childhood activities of Abbot's son Frederic V. Abbot, death of Abbot's brother Edward Stanley Abbot at Gettysburg, Pa., in 1863, and Washington, D.C., social life in 1857. Includes reminiscences about the Abbot family and life in Cambridge, Mass., by Abbot's mother-in-law Emily Everett, recollections of Abbot's childhood by his mother Fanny Larcom Abbot, and a file pertaining to the life of Henry Larcom, shipmaster and Abbot's maternal grandfather, including Larcom's survival of the wreck of the Margaret in 1810 in the North Atlantic during the Napoleonic Wars.
Correspondents include Fanny Larcom Abbot, Joseph Hale Abbot, Mary Susan ("Susie") Everett Abbot, and William Henry Seward.
Library of Congress Prints and Photographs Division.
Army officer. Full name: Henry Larcom Abbot. Born 1831; died 1927.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbot, Edward Stanley, -- 1841-1863.; Abbot, Fanny Larcom, -- 1807-1883 -- Correspondence; Abbot, Frederic V. -- 1858-1928.; Abbot, Jos. Hale -- 1802-1873 -- Correspondence; Abbot, Mary Susan Everett, -- 1832-1871 -- Correspondence; Everett, Emily, -- 1799-; Grant, Ulysses S. -- 1822-1885.; Larcom, Henry, -- 1777-1862.; Lincoln, Abraham, -- 1809-1865.; McClellan, George Brinton, -- 1826-1885.; Seward, William Henry, -- 1801-1872 -- Correspondence; Abbott family -- Correspondence; United States. -- Army -- Ordnance and ordnance stores; United States. -- Army. -- Corps of Engineers; United States. -- President (1861-1865 : Lincoln).; Margaret (Ship); Bull Run, 1st Battle of, Va., 1861.; Fortification -- Washington (D.C.) -- History -- 19th century; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Napoleonic Wars, 1800-1815.; Peninsular Campaign, 1862.; Cambridge (Mass.) -- Social life and customs -- 19th century; Massachusetts -- History -- Civil War, 1861-1865.; Petersburg (Va.) -- History -- Siege, 1864-1865.; Richmond (Va.) -- History -- Siege, 1864-1865.; United States -- History -- Civil War, 1861-1865 -- Artillery operations; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Causes; United States -- History -- Civil War, 1861-1865 -- Participation, African American; United States -- History -- Civil War, 1861-1865 -- Technology; United States -- Politics and government -- 1861-1865.; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Washington (D.C.) -- Social life and customs -- 19th century; Army officers